2016
DOI: 10.1371/journal.pone.0151726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Gentle, Self-Administered Stimulation of Perineal Skin for Nocturia in Elderly Women: A Randomized, Placebo-Controlled, Double-Blind Crossover Trial

Abstract: BackgroundSomatic afferent nerve stimuli are used for treating an overactive bladder (OAB), a major cause of nocturia in the elderly. Clinical evidence for this treatment is insufficient because of the lack of appropriate control stimuli. Recent studies on anesthetized animals show that gentle stimuli applied to perineal skin with a roller could inhibit micturition contractions depending on the roller’s surface material. We examined the efficacy of gentle skin stimuli for treating nocturia.MethodsThe study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Based on their ndings, we had expected the contact acupuncture to be superior to the sham acupuncture ; however, this was not the case herein. Another study found that cutaneous stimulation with a roller made of the same material as the sham acupuncture device used in the present study was effective for treating overactive bladder-related nocturia in elderly women 25 . Further investigations of stimulation modalities are needed, including the degree of skin compression and the stimulation materials.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Based on their ndings, we had expected the contact acupuncture to be superior to the sham acupuncture ; however, this was not the case herein. Another study found that cutaneous stimulation with a roller made of the same material as the sham acupuncture device used in the present study was effective for treating overactive bladder-related nocturia in elderly women 25 . Further investigations of stimulation modalities are needed, including the degree of skin compression and the stimulation materials.…”
Section: Discussionmentioning
confidence: 51%
“…In recent years, studies have demonstrated the effects of pleasant touch on single afferent ber activities in cutaneous nerves [22][23][24][25] . Pleasant touch activates mechanoreceptors in the skin 23 , which changes autonomic function, and suppresses stress [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that noninvasive gentle stimulation applied to the perineal skin of anesthetized rats with an elastomer roller without microcones was effective for inhibiting micturition contractions, whereas stimulation applied with a polystyrene roller having a hard surface was ineffective. 12,13 In the future, more-detailed studies need to be conducted with various skin-stimulation devices to assess the effects of the presence or absence of microcones, the size and sturdiness of the device, the materials used in the device, and other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the participants with OAB, nighttime urination frequency significantly decreased from baseline during the active stimulation period compared to that during the placebo stimulation period (Fig. A) (Iimura et al, ). In contrast, micturition frequency was not affected by either stimulus in participants without OAB (Fig.…”
Section: Clinical Effects Of Gentle Skin Stimulation In Community‐dwementioning
confidence: 99%